PRAKTEK QARDH DI BANK WAKAF MIKRO ALPEND BAROKAH MANDIRI PERSPEKTIF ISLAM, PEMBERDAYAAN UMKM (Studi di BWM Al-Amien Prenduan) - Ibnu Kusuma Negara; Sriyati Sriyatin (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
ABSTRACTThe purpose of his research is to find out and analyze the practice of the qardh in Islamic perspective, and the impact of the practice of financing with the Qardh contract on empowerment UMKM , as well as supporting and inhibiting factors and solutions of the empoerment. This research uses descriptive qualitative research with a phenomenological approach as the main theoretical basis. The data collection techniques used interviews, observation, documentation, about the practice of Qardh Practices at the Bank Wakaf Mikro Alpen Barokah Mandiri Islamic Perspective in empowerment Small and Medium Businesses (UMKM) Around the Boarding School. The collected data is then managed and analyzed using descriptive qualitative.Â Keywords : Qardh Practice, Impact, Empowerment Of Supporting Factors, Inhibiting Factors